Kompetansi Pedagogik Guru PAI Dalam Mendesain Pembelajaran Pasca Pandemi Covid-19 di MAN Kota Pariaman - Rahmad Agung; Ahmad Sabri; Sasmi Nelwati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research is based on the post-covid-19 pandemic which has brought many changes to the learning process for teachers and students. In the learning process, teachers must design and prepare thorough learning plans to achieve goals. post-Covid 19 pandemic at MAN Kota Pariaman. The goal is 1); What is the pedagogical competence of PAI teachers after the Covid-19 pandemic?; 2), How do PAI teachers apply it in designing learning?; 3) What are the supporting and inhibiting factors for pai teachers in improving pedagogical competence after the Covid-19 pandemic at MAN Kota Pariaman. This research uses a descriptive qualitative method, namely describing events in the field through data collection tools such as observation, documentation and interviews. The results are 1) Post-pandemic teachers' pedagogical competence is quite optimal in designing learning and in using digitalization technology in the learning process in the digitalization era at MAN Kota Pariaman; 2) The implementation of post-pandemic learning design is quite optimal with methods, strategies and learning models that can adapt to the character of students at MAN Kota Pariaman; 3) The supporting factor for PAI teachers in developing post-pandemic pedagogical competence is that school principals hold workshop training for PAI teachers in using digitalization technology. Meanwhile, the inhibiting factors are the lack of digitalization training held by the school and the lack of projectors in each class to support the learning process.